Del sepulcro al germen: El Cuzco Paqarina como tejido-partitura en cinco movimientos (1913-1927). El aporte de Luis E. Valcárcel - López Lenci, Yazmín (Revista Letral, 2012)
In 1925 Luis E. Valcarcel is publishing in Lima De la Vida Inkaica, book that gathers texts written between 1913 and 1924 and that will be considered by its author as the first exhibition of his "indigenista ideology"; for after publishing in 1927 the decisive book Tempest in the Andes, considered within the peruanista corpus as a milestone within the modern andean thought and a figure of the limits of the debates of the arts, literatures and the social sciences in an era of the rise of the Avant-garde in Latin America. The text outlines a mobile genealogy of andean critical and literary thinking from these books to understand its complexities in the birth of the project Cuzco Paqarina, which I propose as a category of analysis that would replace the of the so-called "Indigenismo Cuzqueño".